Analysis Efficiency of Islamic Banking Financing in Improving Sustainability Performance and Green Banking in Indonesia - Lia Dahlia Iryani; Erwin Erwin; Muhammad Wahyu Akbar (Faculty of Islamic Business and Management, 2023)
This study aims to analyze the efficiency of Islamic banking financing in increasing sustainability performance and green banking in Indonesia. This study used 34 Islamic banking institutions through filling out questionnaires by the heads of the accounting and reporting divisions. The data was processed and analyzed using Structural Equation Modeling (SEM). The results of the study show that the efficiency of Islamic banking financing has a positive effect on increasing sustainability performance and green banking in Indonesian Islamic banking. Improved sustainability performance and green banking caused by the financing return strategy carried out by Islamic banking can help companies to obtain information from financial performance so that they can plan suitable strategies in the future and Islamic banking can focus on community welfare through environmental preservation.